Dose-response relations between Purpureocillium lilacinum PLSAU-1 and Meloidogyne incognita infecting brinjal plant on plant growth and nematode management: a greenhouse study - Most. Sinthia Sarven (Egyptian Journal of Biological Pest Control, 2019)
Abstract The efficacy of various doses of Purpureocillium lilacinum PLSAU-1 (P. lilacinum PLSAU-1) was evaluated against brinjal root-knot pathogen, Meloidogyne incognita (M. incognita) at different inoculum levels. Experimental pot soil was treated by four doses (0, 1 ×  105, 5 × 105, and 1 × 106 CFU/g soil) of P. lilacinum PLSAU-1 before transplanting, and 5 inoculum levels of M. incognita (0, 100, 400, 800, 1600, and 3200 eggs per 100 cm3 soil) were used after 3 days of brinjal transplantation. A significant correlation was observed between doses of P. lilacinum PLSAU-1 and inoculum densities of M. incognita. Among the doses, the rate of P. lilacinum PLSAU-1 of 1 × 106 CFU/g soil enhanced highly plant growth parameters. Inoculation of M. incognita reduced plant growth significantly, and the reduction increased with the increase of inoculum density of M. incognita. The application of P. lilacinum PLSAU-1 at 1 × 106 CFU/g soil reduced a maximum of 72% gall index and 84% egg masses when the crop was challenged by 800 and 400 eggs/100 cm3 soil, respectively. The dose of 1 × 106 CFU/g soil of P. lilacinum PLSAU-1 showed effectiveness to reduce reproduction factor of M. incognita up to 81% when the crop was inoculated by 800 eggs of the pest/100 cm3 soil. The study demonstrated that P. lilacinum PLSAU-1 is an effective bio-agent for controlling of root-knot nematode on brinjal and can be a key component of environment-friendly management approach.